INBIO - Solórzano, Luis Diego; Flores, Nelson (San José, C.R. : Producciones Audiovise, 1996)
Describe las características del INBIO
Incluye videograbación en inglés y español
Keywords: INSTITUTO NACIONAL DE BIODIVERSIDAD (COSTA RICA); BIODIVERSIDAD -- INVESTIGACIONES